DEVELOPMENT OF INTERACTIVE TEAMS GAMES TOURNAMENT-BASED E-MODULES TO IMPROVE ELEMENTARY STUDENTS’ SOCIAL STUDIES UNDERSTANDING - Risa Tantri; Ismira; Hafiz Hidayat (Universitas Majalengka, 2025)
This study aims to develop an Interactive E-Module based on the Teams Games Tournament (TGT) learning model and to test its validity, practicality, and effectiveness in improving elementary students’ understanding of social studies concepts. The study is motivated by the limited use of interactive learning media in social studies, which causes students to memorize facts rather than comprehend concepts deeply, leading to low motivation, limited engagement, and weak critical thinking skills. The research employs the Research and Development (R&D) approach using the ADDIE model, encompassing the stages of Analysis, Design, Development, Implementation, and Evaluation. The subjects involved fifth-grade students of SDN 02 Percontohan and SDN 04 Garegeh, social studies teachers, and expert validators in material, media, and language. Data were collected through observations, questionnaires, interviews, tests, and documentation, and analyzed both qualitatively and quantitatively. The results indicate that the Interactive E-Module achieved a very valid category with an average expert validation score of 4.56. The practicality assessment showed very positive responses from teachers (90.5%) and students (90.8%). Moreover, its effectiveness was evidenced by a significant improvement in conceptual understanding, with an average N-Gain score of 0.87 (high category). The TGT-based Interactive E-Module offers a novel contribution by integrating cooperative competition into digital learning media, enhancing student motivation and interaction beyond conventional e-modules. Practically, this module can be adapted for other subjects or educational levels as an innovative tool to promote active, engaging, and concept-oriented learning in elementary education.